Robust and efficient ultrasound video coding in noisy channels using H.264 - Panayides, Andreas S.; Pattichis, Marios S.; Pattichis, Constantinos S.; Loizou, Christos P.; Pantziaris, Marios; Pitsillides, Andreas (My University, 2009)
In this paper we define diagnostic Regions of Interest (ROIs) for carotid ultrasound medical video, which we then use as input for Flexible Macroblock Ordering (FMO) slice encoding. We extend the FMO concept by enabling variable quality slice encoding, tightly coupled by each region's diagnostic importance. Redundant Slices (RS) utilization increases compressed video's resilience over error prone transmission mediums. We evaluate our scheme on a series of five (5) carotid ultrasound videos at QCIF and CIF resolutions, for packet loss rates up to 30%. Quality assessment based on a clinical rating system that provides for independent evaluations of the different parts of the video (subjective), as well as PSNR ratings (objective), shows that encoded videos attain enhanced diagnostic performance under noisy environments, while at the same time achieving significant bandwidth demands reductions.
Keywords: Error resilience; FMO; H.264; Redundant slices; ROI segmentation; Ultrasound video